Clinical Prescription-Protein-Small Molecule-Disease Strategy (CPSD), A New Strategy for Chinese Medicine Development: A Case Study in Cardiovascular Diseases - Guo, Yong-Zhi; Jiang, Ying-Nan; Li, Yi-Fang; Kurihara, Hiroshi; Dai, Yi; He, Rong-Rong (Frontiers in Pharmacology, 2020)
Chinese medicine, an important part of Traditional Chinese Medicine, is a wisdom given by Chinese ancestors, bringing health to the Chinese people and even the people around the world. However, the mystery of Chinese medicine and its enormous difference with western medicine are the great obstacle to the internationalization of Chinese medicine. Here, we first proposed the clinical prescription-protein-small molecule-disease strategy (CPSD) strategy, a Traditional Chinese Medicine development strategy for quickly discovering therapeutic drugs from clinical prescriptions, which is a bridge gapping Chinese medicine and western medicine. The application of CPSD strategy was exemplified in the development of anti-cardiovascular diseases drugs. CPSD strategy may provide new ideas for the development of Chinese medicine and even for new drugs.